Peniophora salaccae sp. nov. (Russulales, Basidiomycota), a snake fruit (Salacca zalacca) pathogen from southern Thailand - Boukaew, Sawai; Kumla, Jaturong; Suwannarach, Nakarin (Phytotaxa, 2024)
The genus Peniophora is known to be distributed from boreal to tropical regions worldwide. During surveys of plant diseases in southern Thailand in 2022 and 2023, two specimens of rotten snake fruits (Salacca zalacca) were collected. The new species, P. salaccae, is described based on collections with morphological and molecular data. This species is characterized by orange-gray to brownish-orange basidiomes, simple-septate generative hyphae, brown lamprocystidia, subclavate to subcylindrical gloeocystidia, and subtriangular basidiospores. It can be distinguished from P. trigonosperma by its larger basidiospores and shorter lamprocystidia. Molecular phylogenetic analyses of the internal transcribed spacers (ITS) and the large subunit (nrLSU) of the nuclear ribosomal DNA (rDNA) confirmed the position of the new species within the genus Peniophora. The full description, color photographs, illustrations, and the phylogenetic tree showing the position of P. salaccae are provided. Additionally, pathogenicity tests showed that P. salaccae could infect snake fruits, which developed the same symptoms under artificial inoculation conditions as those observed in the field.